Mapping points of interest: an analysis of students' engagement with digital primary sources. Issue 3 (3rd July 2018) - Rysavy, Monica D. T.; Michalak, Russell; Hunt, Kevin
ABSTRACT: The Digital Archival Advertisements Survey Process (DAASP) model is a collaborative active learning exercise designed to aid students in evaluating primary source documents of print-based advertisements. By deploying DAASP, the researchers were able to assess the students' ability to evaluate their biases of the advertisements in a first-year composition course. This research attempts to answer the following research question: Do students perceive heatmap-centered collaboration as helpful with their evaluation of library-licensed digital primary sources? This research explored students' experiences interacting with and reflecting on archival advertisements (mid-twentieth century) in a first-year composition class in Fall 2017 utilizing the DAASP model.